Case of Ruptured Ectopic Pregnancy in the Uterosacral Ligament and Review of the Literature - Yasmin Abedin; Kanchi Chadha (Case Reports in Obstetrics and Gynecology)
Pregnancies that implant on the uterosacral ligament are rare. Here, we describe a case of ruptured ectopic pregnancy in the left uterosacral ligament in a patient with potential risk factors including possible endometriosis and recent hysteroscopic procedure. A 29-year-old female, para 0, presented to the emergency department with generalized abdominal pain. Pelvic examination was significant for fullness in the posterior cul-de-sac. Laboratory values were significant for beta-human chorionic gonadotropin (hCG) level of 6311 mIU/mL. Sonogram findings were significant for no intrauterine gestation, a 6.9×4.6×4.7 cm3 complex left adnexal mass, and moderate free fluid within the posterior cul-de-sac. The patient underwent laparoscopy, which revealed hemoperitoneum and unremarkable bilateral fallopian tubes and ovaries. An abnormal area was noted in the left uterosacral ligament. Tissue was bluntly removed and pathologically confirmed as chorionic villi within the left uterosacral ligament. After one week, her beta-hCG decreased to 784 mIU/mL. After two weeks, she was seen as an outpatient and was doing well without any symptoms. More information is required regarding these unique pregnancies to help understand the pathophysiology and determine the management.